An observational study to determine the incidence and the clinico-epidemiologic profile of dengue fever in paediatric age group presenting to a tertiary care centre in Western Rajasthan, India - Kumari, Sangeeta; Makwana, Mohan; Mourya, Harish Kumar; Mitharwal, Ramavtar; Ram, Shivji; Meena, Anju; Patel, Polesh (International Journal of Contemporary Pediatrics, 2020)
Background: Dengue remains major public health concern because of the expanding geographic distribution of both the virus and the mosquito vector. Aims and objectives was to determine the incidence of dengue fever in paediatric age group presenting to a tertiary care centre in Western Rajasthan and to evaluate the clinico-epidemiologic profile of these children. Methods: This is observational epidemiological study on patients of pediatric age group, over a period of one year. Results: A total of 210 ELISA positive cases, comprising of 55% males and 45% female (Male to female ratio of 1.2:1) were enrolled. In this study most (44.7%) were age group of 10-18 years, 80% patients from urban area, 93.8%. admitted between the months of September to December, 70.95% presented between 3rd to 5th days of their illness, 48 (22.86%) were tourniquet test positive at the time of admission with fever being most common (95.23%) presenting symptom, followed by headache (60%) and vomiting (55%). Almost all (99.52%) had thrombocytopenia (34.2% of them had severe thrombocytopenia), most (85%) had a hospital stay of less than a week, 98.10% patients required fluid therapy for less than 5 days. and a mean of 3.41±2.60 days were required by these patients to recover from significant thrombocytopenia. Here 22% (46) patient’s required ICU care, with shock being main indication for ICU admission, followed by requirement of blood product transfusion (73%). Bleeding manifestations were seen in 73(34%) patients, commonest being the epistaxis in 40 patients (55%). Conclusions: Incidence of dengue was 0.42% with 32.38%patients were IgG ELISA positive also.